2005
DOI: 10.1111/j.1467-8624.2005.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Discipline and Children's Adjustment: Cultural Normativeness as a Moderator

Abstract: Interviews were conducted with 336 mother -child dyads (children's ages ranged from 6 to 17 years; mothers' ages ranged from 20 to 59 years) in China, India, Italy, Kenya, the Philippines, and Thailand to examine whether normativeness of physical discipline moderates the link between mothers' use of physical discipline and children's adjustment. Multilevel regression analyses revealed that physical discipline was less strongly associated with adverse child outcomes in conditions of greater perceived normativen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
413
2
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(450 citation statements)
references
References 52 publications
27
413
2
8
Order By: Relevance
“…Consistent with the cultural emphasis on parents' firm control and filial piety in traditional East Asian societies (Wu et al, 2002), researchers found that the cultural norms of parental authoritarian control are higher in East Asian than in Western cultures (Lansford et al, 2005). Indeed, comparative studies showed that native or immigrant Chinese parents endorsed higher authoritarian parenting and lower authoritative parenting than European American parents (e.g., Dornbusch, Ritter, Leiderman, Roberts, & Fraleigh, 1987;Wu et al, 2002).…”
Section: Parenting As a Mediator In The Relations Between Cultural Ormentioning
confidence: 77%
“…Consistent with the cultural emphasis on parents' firm control and filial piety in traditional East Asian societies (Wu et al, 2002), researchers found that the cultural norms of parental authoritarian control are higher in East Asian than in Western cultures (Lansford et al, 2005). Indeed, comparative studies showed that native or immigrant Chinese parents endorsed higher authoritarian parenting and lower authoritative parenting than European American parents (e.g., Dornbusch, Ritter, Leiderman, Roberts, & Fraleigh, 1987;Wu et al, 2002).…”
Section: Parenting As a Mediator In The Relations Between Cultural Ormentioning
confidence: 77%
“…Cultural factors may also affect perceptions of a 'normally' functioning family, 'harsh' parenting and child behaviour. For instance, studies have shown that physical punishment is more accepted in some cultures than in others possibly leading to differences in the threshold to report harsh parenting [42].…”
Section: Discussionmentioning
confidence: 99%
“…Some questions have been raised regarding the cross-cultural generalizability of authoritative and authoritarian parenting and their implications for child adjustment. For example, in cultures where the perceived norms for authoritarian parenting (e.g., use of physical discipline) are higher (e.g., African American culture), authoritarian parenting was less strongly related to negative child adjustment than in the Euro-American culture (Deater-Deckard, Dodge, & Sorbring, 2005;Steinberg, 2001), although the overall negative relation of physical discipline to adjustment was evident in multiple cultures (Lansford et al, 2005). Chao (1994Chao ( ,2001 proposed that authoritative and authoritarian parenting may not fully capture the important features of Chinese parenting and that an indigenous construct such as "guan" or training should be considered.…”
Section: Generalizability Of the Model To Chinese Familiesmentioning
confidence: 99%